A new rainfrog of the Pristimantis myersi Group (Amphibia, Craugastoridae) from Volcán Pichincha, Ecuador - Rojas-Runjaic, Fernando (2014)
A new frog of the Pristimantis myersi Group is described from a bamboo patch within the Reserva Ecológica Verdecocha (0°5'46.9″S, 78°36'15.3″W; 2851 m), located at northwestern flank of the Volcán Pichincha, in the vicinities of Quito, Ecuador. The new species is known from eight adult males, whereas the females remain unknown; it can be readily distinguished from all species of the P. myersi Group that inhabit the highlands of the Ecuadorian Andes by the unique combination of the following characters: body small (adult male SVL 14.9-19.7 mm; females unknown); dorsal skin shagreen, with a barely visible middorsal raphe, scapular and dorsolateral folds; tympanum small but well-defined; upper eyelid with one enlarged tubercle; males with prominent vocal slits, but without nuptial pads on thumbs; fold-like tarsal tubercles. With this new species, the number of Pristimantis assigned to the P. myersi Group raises to 16, of which, 12 are in Ecuador. We provide notes on morphology and color variation, advertisement call, and natural history of the new species. © 2014 Magnolia Press.